Blending Plan Batubara Sulfur Tinggi dengan Kandungan Sulfur Rendah - Sudrajat, Asep; Erwin Wijaya, Andy (ReTII, 2024)
Blending coal is one of the methods to optimize the characteristics of coal by mixing coal of various qualities. This research aims to reduce the sulfur content in high-calorie coal with high sulfur content, using low-calorie coal with lower sulfur content. With this method, it is expected to produce a coal mixture with lower sulfur content, without significantly sacrificing calorific value, and to increase the market acceptance of coal with more environmentally friendly sulfur content.